Himachal Pradesh Development Report - Planning Commission (Planning Commission, 2005)
The State Development Report (SDR) on Himachal Pradesh is different from the earlier report on Punjab, though both were prepared by the Centre for Research in Rural and Industrial Development (CRRID), Chandigarh. The report on Punjab has taken into account the history of 2000 years of the region and focuses on the past, the present and the future. The one on Himachal Pradesh has its focus primarily on the future
Planning Commission Government of India
Planning Commission Government of India